Analysis of Perception and Practice of Implementation of SAK EMKM In Preparation of Financial Reports of Bumdes Karya Abadi, Penambangan Village, Balongbendo - Yuvita Aprilia Hariyanti; Putikadea, Insyirah (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) is a guideline designed to improve the quality of financial statements in small-scale entities, including Village-Owned Enterprises (BUMDes). This study aims to analyze the perceptions and practices of managers towards the implementation of SAK EMKM at BUMDes Karya Abadi, Penambangan Village, Balongbendo District. This research uses a descriptive qualitative method with data collection techniques through interviews and the distribution of questionnaires. Respondents in this study are active managers of BUMDes who are directly involved in the process of preparing financial statements. Data were analyzed by descriptive statistics to measure trends in perceptions and practices, and thematically analyzed to interpret open-ended answers. The results show that the managers' perceptions towards the implementation of SAK EMKM are very positive as indicated by the dominance of high scores on the perception indicators. On the other hand, management practices also show consistency in the application of accounting standards in recording transactions, preparing reports, and team involvement. This finding strengthens previous research which states that the application of SAK EMKM can improve the accountability, structure, and transparency of BUMDes' financial statements. The main obstacle encountered is limited technical understanding, indicating the need for ongoing assistance.